Directivity and Bandwidth Enhancement of Proximity-Coupled Microstrip Antenna Using Metamaterial Cover - Veysi, Mehdi; Jafargholi, Amir (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Two major problems associated with patch antennas are low gain and narrow bandwidth. This paper is mainly concerned with directivity and bandwidth enhancement of proximity-coupled microstrip antenna using metamaterial cover. Compared to the patch without metamaterial cover, bandwidth of the antenna is improved about 2.33% and directivity is increased about 9.91dB. The commercial software CST Microwave Studio and a full-wave FDTD numerical technique, developed by the authors, are adopted for the simulations.